(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines fundamental aspects of vocabulary in writers’ literary works. It explores how the core lexical system reflects individual characteristics of an author’s style, their ideological and artistic objectives, and preferences in selecting linguistic means. Particular attention is given to stable linguistic elements that recur across various texts and their role in shaping the author’s worldview. The study employs both quantitative and qualitative analysis of lexical units belonging to the core vocabulary, aiming to identify patterns in their usage. The research concludes that the core vocabulary performs not only a communicative function but also a stylistic one, reflecting the distinctive features of the writer’s creative manner. This work addresses linguists and literary scholars, examining issues of authorial style and the linguistic structure of literary texts.